Effects of intra-operative administration of intravenous dexmedetomidine on incidence of emergence phenomenon after general anaesthesia in adults; An observational study - Bhat, Ghulam Jeelani; Naqash, Iqra Nazir; Lone, Abdul Qayoom; Faizah Mufti; Ganie, Farooq Ahmad; Mir, Altaf Hussain; Qadri, Reyaz (Asian Journal of Medical Sciences, 2023)
Background: The occurrence of emergence agitation (EA) is the most common and practical problem faced in the immediate post-operative period during the process of Extubation under General Anaesthesia. Dexmedetomidine, an α2 adrenoceptor agonist is an excellent drug that has been shown effective to decrease the preoperative anxiety and smooth induction and emergence. Aims and Objectives: To assess the effect of intravenous dexmedetomidine primarily on EA and other complications that may occur during emergence from general anesthesia. Materials and Methods: 80 patients of either gender aged 18–65 years with ASA status I and II, undergoing various elective general and urological surgeries under general anesthesia were included in the study. Patients receiving adjuvant drug dexmedetomidine, were labelled as Group D (n=40) and those who didn’t receive any adjuvant were labelled as group C (n=40). Dexmedetomidine was given at 1 μg/kg and then maintained at infusion of 0.4 μg/kg/h till the end of the surgery for group D. The hemodynamic parameters and SpO2 were measured during the intraoperative period at various intervals of time till the end of surgery and also on arrival to the recovery room till patient was discharged from post-anesthesia care unit in both the groups. Results: The use of IV dexmedetomidine has proved significantly effective in prevention of incidence of EA with the overall incidence of agitation of 7.5% in Group D as compared to 42.5% in group C. Conclusion: Intraoperative administration of intravenous dexmedetomidine decreased the incidence of EA and other emergence phenomena like cough, pain and PONV with stable hemodynamics, safety profile, good analgesic properties and opioids sparing side effects.